Clinical Application of Oral Meglumine Diatrizoate Esophagogram in Screening for Esophageal Fistula During Radiotherapy or Chemoradiotherapy for Esophageal Cancer - Wu, Rong; Geng, Lidan; Zhao, Zhenhua; Liao, Dongbiao; He, Bin; Hu, He; Lin, Yanqun; Li, Musheng; Xiang, Miao; Zhang, Yu; Feng, Gang; Tan, Bangxian; et al. (Frontiers in Oncology, 2020)
Background: This study aimed to investigate the specificity and sensitivity of oral meglumine diatrizoate esophagogram in screening for esophageal fistula during radiotherapy or chemoradiotherapy for esophageal cancer and determine if early detection and intervention could improve the prognosis of esophageal fistulas. Methods: Esophageal cancer patients undergoing radiotherapy or chemoradiotherapy were included. Weekly oral meglumine diatrizoate esophagograms were performed to screen for esophageal fistulas during radiotherapy. When an esophageal fistula was detected, fibro-esophagoscopy and computed tomography (CT) were used for confirmation; once confirmed, radiotherapy was discontinued, and the patient received intervention. The esophagogram results were reviewed weekly to assess the recovery of the esophageal fistula. If the fistula was healed, the patient resumed and completed radiotherapy. Results: A total of 206 patients with cancer of the esophagus undergoing chemotherapy/radiotherapy were included. During radiotherapy, 10 cases of esophageal fistula were detected or suspected based on the oral meglumine diatrizoate esophagography findings, and eight of those cases were confirmed by CT and esophagoscopy. All patients with esophageal fistula received intervention; among them, 62.5% (5/8) recovered after 1−2 weeks of treatment and continued radiotherapy to completion. The sensitivity and specificity of oral meglumine diatrizoate esophagography in screening for esophageal fistulas during radiotherapy or chemoradiotherapy was 100% and 98.9%, respectively. The median survival period of patients with esophageal fistulas was 6.4 months. Conclusion: Oral meglumine diatrizoate esophagography has high sensitivity and specificity in screening for esophageal fistulas during radiotherapy or chemoradiotherapy with minimal side effects. Early diagnosis and timely intervention can significantly improve the prognosis and prolong the survival period of patients.